Bone Geometry, Volumetric Density, Microarchitecture, and Estimated Bone Strength Assessed by HR‐pQCT in Adult Patients With Type 1 Diabetes Mellitus. (20th July 2015) - Shanbhogue, Vikram V; Hansen, Stinus; Frost, Morten; Jørgensen, Niklas Rye; Hermann, Anne Pernille; Henriksen, Jan Erik; Brixen, Kim
ABSTRACT: The primary goal of this cross‐sectional in vivo study was to assess peripheral bone microarchitecture, bone strength, and bone remodeling in adult type 1 diabetes (T1D) patients with and without diabetic microvascular disease (MVD+ and MVD–, respectively) and to compare them with age‐, gender‐, and height‐matched healthy control subjects (CoMVD+ and CoMVD–, respectively). The secondary goal was to assess differences in MVD– and MVD+ patients. Fifty‐five patients with T1DM (MVD+ group: n = 29) were recruited from the Funen Diabetes Database. Dual‐energy X‐ray absorptiometry (DXA), high‐resolution peripheral quantitative computed tomography (HR‐pQCT) of the ultradistal radius and tibia, and biochemical markers of bone turnover were performed in all participants. There were no significant differences in HR‐pQCT parameters between MVD– and CoMVD– subjects. In contrast, MVD+ patients had larger total and trabecular bone areas ( p = 0.04 and p = 0.02, respectively), lower total, trabecular, and cortical volumetric bone mineral density (vBMD) ( p < 0.01, p < 0.04, and p < 0.02, respectively), and thinner cortex ( p = 0.03) at the radius, and lower total and trabecular vBMD ( p = 0.01 and p = 0.02, respectively) at the tibia in comparison to CoMVD+. MVD+ patients also exhibited lower total and trabecular vBMD (radius p = 0.01, tibia p < 0.01), trabecular thickness (radius p = 0.01), estimated bone strength, and greater trabecular separation (radius p = 0.01, tibia p < 0.01) and network inhomogeneity (radius p = 0.01, tibia p < 0.01) in comparison to MVD– patients. These differences remained significant after adjustment for age, body mass index, gender, disease duration, and glycemic control (average glycated hemoglobin over the previous 3 years). Although biochemical markers of bone turnover were significantly lower in MVD+ and MVD– groups in comparison to controls, they were similar between the MVD+ and MVD– groups. The results of our study suggest that the presence of MVD was associated with deficits in cortical and trabecular bone vBMD and microarchitecture that could partly explain the excess skeletal fragility observed in these patients. © 2015 American Society for Bone and Mineral Research.